Biometric Measures, Body Score and Body Mass Index Evaluation in Wild Coatis (Nasua Nasua) Living in the South-Central Region of São Paulo State, Brazil - Sardela Ferro, Barbara; Giolo Hippólito, Alícia; Reis Castiglioni, Maria Cristina; de Siqueira Silva Junior, José Ivaldo; Teixeira, Carlos Roberto; Baldissera Gonçalves, Raphael Augusto; Charas dos Santos, Ivan Felismino; de Vasconcelos Machado, Vânia Maria; Chalfun Guimarães Okam, Priscylla Tatiana; Melchert, Alessandra (Acta Scientiae Veterinariae, 2019)
Background: Coatis (Nasua nasua) have easy interaction with man, besides being sociable and curious animals. The proximity to urbanized areas encourages them to intake food from anthropogenic sources, and it can change their eating habits and make them prone to obesity. The body condition evaluates the animals’ energetic status and measures variations in their body fat reserves. There are direct-invasive methods and indirect methods that rely on size and body mass to evaluate the body condition, like body condition score and body mass index. Thus, the aim of the present study was to assess different methods to determine the body condition of wild coatis (Nasua nasua) living in urban areas. Materials, Methods & Results: Sixteen (16) wild coatis (Nasua nasua), nine females and seven males, were captured at Faculty of Veterinary Medicine and Animal Science (FMVZ) of São Paulo State University, Botucatu, in pitfalls. The animals were anesthetized with ketamine and midazolam and subjected to biometric evaluation after physical exams proved normal. The following variables were analyzed: body weight, body condition score (BCS) based on the five-point scale for dogs, thoracic and abdominal circumference, height at the withers, spine length and distance from the patella to the calcaneus. Two body mass index (BMI) were calculated from these data, one was based on dogs (BMI1) and another one on cats (BMI2), as well as the body fat percentage (%BF). Results showed that 25% of the assessed coatis were overweight. Body weight, thoracic and abdominal circumference, height at the withers, spine length and distance from the patella to the calcaneus were significantly higher in males than in females and the other assessed parameters did not present differences between sexes. The correlation between fat percentage and body weight was significant, and that between fat percentage and BCS was not. There was closer correlation between BMI2 and body weight, and BCS, than between BMI1 and these two parameters. Discussion: Anthropogenic interactions could change the body condition of these animals and make them prone to obesity, since their body condition scores were altered. With regard to the nutritional body condition, although males were bigger than females, the measures did not show significant differences between them. Results of this parameter varied in different studies with coatis, some studies have shown that males have body mass 1/3 higher than that of females and others have not recorded any difference between sexes. Fat percentage estimated through the metrics used in cats is not a good method when it is applied alone in body condition evaluations. A study that has correlated body mass, body condition score, body fat estimates, body mass index and abdominal circumference recorded positive results between these two evaluation methods. Such finding corroborated with the present study, but it was differed from it in abdominal circumference, which did not correlate to the two body mass indices and to body fat percentage. Therefore, it is possible saying that there is biometric difference between male and female coatis. The body condition score adopted for dogs was efficient for coatis (Nasua nasua), as well as the body mass index used for dogs and cats – the one used for cats was even more efficient. The proximity wild coatis (Nasua nasua) have to humans could change the body condition of these animals and make them prone to obesity.